Destination Marketing Application as an Innovative Instrument for Sustainable Urban Development (According to the Example of Pleven) - Tsvetanova, Eva (Research Papers, 2018)
The article investigates the role of destination marketing in the process of sustainable urban development. The tourism potential of sites related to the cultural and historical heritage of Pleven is analyzed as well as the factors preventing or favoring organization of destination marketing activities in Pleven. As a result of empirical analysis, the specific proposals are defined to assist local authorities in creating a favorable local environment for enhancing entrepreneurial activity to achieve sustainable growth in the field of cultural and heritage tourism.Jel: R58, Z32, O18
Keywords: Destination marketing; Sustainable urban development; Cultural and heritage tourism; Territorial segmentation